Impact of Religiosity and Tax Penalties on Taxpayer Compliance: The Mediating Role of Taxpayer Awareness - Ramli, Ahmad; Yusup, Muhamad; Sanurdi, Sanurdi (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study examines how religiosity and tax penalties influence taxpayer compliance, with taxpayer awareness as an intervening variable in the land and building tax (PBB) in Mataram City. Methodology: The Partial Least Square-Structural Equation Model (PLS-SEM) approach was used to assess both the measurement and structural models. The data was collected through a questionnaire with 100 respondents using purposive sampling techniques.   Results: Taxpayer awareness significantly influences taxpayer compliance. Religiosity directly affects taxpayer compliance but does not influence taxpayer awareness. Tax penalties influence taxpayer awareness but not taxpayer compliance. Taxpayer awareness mediates the relationship between tax penalties and taxpayer compliance but not mediates the relationship between religiosity and taxpayer compliance. Findings: There is a positive and significant direct influence of the taxpayer awareness variable on taxpayer compliance and religiosity on taxpayer compliance. Tax penalties positively and significantly indirectly influence taxpayer compliance, with taxpayer awareness as an intervening variable. Novelty: The study integrates internal (religiosity) and external (tax penalties) factors in taxpayer behavior. Originality: Provides empirical insights on why tax penalties influence awareness but not direct compliance. Conclusion: Strengthening taxpayer awareness is crucial in improving compliance. The role of religiosity in taxation is inconsistent and varies by perception. Type of Paper: Empirical research paper.